DEMONSTRATION OF FRESH AND HEALTHY DRINKS PRODUCTION MADE FROM MEDICINAL PLANTS OF THE RHIZOME TYPES - Supriyadi Supriyadi; Novita Dewi; Neni Maemunah; Errick Endra Cita; Zuhdi Ma’sum (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The implementation of community service aims to increase the knowledge and skills of participants in processing rhizomes into a fresh and healthy drink, rhizome types are believed to have benefits and efficacy to help improve health. Improving the knowledge and skills of participants can be done by providing training through demonstrations and mentoring by giving participants the opportunity to try making fresh and healthy drinks made from rhizomes. The implementation of this community service activity was attended by PKK members in Sidorejo Village, Jabung District, Malang Regency with a total of 31 participants. This activity takes place for 2 days, starting from 04 to 05 September 2021 at the DEWISRI Tourist Location (Desa Wisata Sidorejo Indah). The first day of community service activities; participants were given a pre-test before the presentation of the material, the results of the pre-test showed that most of the participants' knowledge of making fresh and healthy drinks made from rhizomes was still lacking. Then after the pre-test presentation of the material and demonstration from the video. second day activities; participants were given a post-test and participants were given the opportunity to practice making fresh and healthy drinks made from rhizomes, in practice the participants were evaluated by the presenters with a check list sheet. Based on the results of the post-test and practice, it was shown that the knowledge, skills and abilities of the participants had increased. After the community service activities take place, it is hoped that participants can process rhizome ingredients into a fresh and healthy drink to increase family immunity, besides that participants can also produce these drinks and sell them.